FOLIAR APPLICATION OF IRON AND POTASSIUM ENHANCES GROWTH AND YIELD OF MUNG BEAN (Vigna radita L.) - Al-Issawi, Mohammed Hamdan; Mahdi, Osama H. (Diyala Agricultural Sciences Journal, 2016)
A field experiment was conducted in factorial layout in RCBD in three replications in order to study the effect of potassium and iron on growth and productivity of this crop. The results showed that potassium significantly enhanced all growth and yield characters while the effect of Iron (Fe) was less significant than K but it has accumulative effect which was significant and clear in plant yield. It can be concluded that nutrients must be added as a foliar application as they have progressive effect on growth as well as yield of mung bean. The high concentrations of those two elements were superior to low concentrations, especially in terms of Fe. Therefore it can be recommended to use higher concentrations of them and widen the growth and yield character in future studies.